Video-On-Demand Streaming Services Subscription Antecedents and Consequences: The Uses and Gratifications Theory Approach - Syafira, Shofwah; Dharmmesta, Basu Swastha (Faculty of Economics and Business, Universitas Gadjah Mada, 2024)
Introduction: This study aims to examine the impact of affective gratification, tension release, cognitive gratification, perceived risk, and viewing addiction on subscription behavior as antecedents and its consequence namely customer engagement. Background Problems: The need for satisfaction is a trigger for media use. As time passes, research on media use through use and audience gratification approaches will always be needed, so this should be carried out in the context of streaming services. Novelty: This research focuses on streaming services using the uses and gratifications theory approach. Similar research has focused on the theoretical implications of usage attitudes, but this research has implications for actual usage behavior, namely subscription behavior. Research Methods: Data have been collected using an online survey with purposive sampling and then analyzed using partial least squares structural equation modeling. Findings: The results suggest that only five of the 13 hypotheses proposed are supported. Companionship and cognitive gratification do not affect subscription behavior, while perceived risk did not impact subscription behavior negatively. Conclusion: The results of this study indicate that streaming service subscribers are more concerned with functional benefits, such as service usability, variety of content, entertainment, and relaxation media. Furthermore, the implications of this research provide benefits both theoretically and practically